Peran Analisis Jabatan dalam Organisasi Terhadap Kinerja Karyawan (Literature Review) - Ade Ratri Fitria; Zepanya Veronica Sinaga; Fionna C A Uguy; Jihan Salsabillah; Netty Merdiaty (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The research carried out has the aim of examining the role of job analysis in an organization and its influence on employee performance. Job analysis is a procedure used to determine the demands and duties of a position as well as the characteristics of individuals who are suitable to fill the available positions, so that this job analysis can increase employee effectiveness and performance. The method used in this research is a literature study by reviewing 30 journals related to job analysis and employee performance. The results of this research also show that there is a positive influence between job analysis and increasing employee performance. Other influencing factors in ensuring individuals are matched to appropriate positions such as job descriptions and job specifications play a very important role. Apart from that, this research also found that job analysis also influences increasing employee job satisfaction, which will also increase employee performance. The suggestions in this research are the need for regular updates to job analysis, job integration into human resource management, and also evaluations that impact job analysis on employee performance.